2014
DOI: 10.1002/jsfa.7015
|View full text |Cite
|
Sign up to set email alerts
|

The etiology of oxidative stress in the various species of animals, a review

Abstract: Oxidative stress is the consequence of an imbalance of pro-oxidants and antioxidants leading to cell damage and tissue injury. The exhaustion of antioxidant systems is one of the reasons for the occurrence of oxidative stress, which results in avalanche production of reactive oxygen species (ROS) or free radicals. High oxidative stress is common in organs and tissues with high metabolic and energy demands, including skeletal and heart muscle, liver and blood cells. Stress arises in animals in response to unavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
83
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 77 publications
0
83
0
7
Order By: Relevance
“…Consequently, since foraging bees are exposed to metals contained in pollen or nectar and are known to accumulate them, this species is considered a potential bioindicator (Perugini et al, 2011;Van Der Steen et al, 2012). So far, it is known that metals may induce oxidative stress, i.e., imbalance between the level of pro-oxidant species and antioxidative defense, resulting in lipid peroxidation (Puppel et al, 2014) as observed in Caddisfly larvae Hydropsyche exocellata (Barata et al, 2005) exposed to Cd. The latent long-term exposure of bees to metals deserves further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, since foraging bees are exposed to metals contained in pollen or nectar and are known to accumulate them, this species is considered a potential bioindicator (Perugini et al, 2011;Van Der Steen et al, 2012). So far, it is known that metals may induce oxidative stress, i.e., imbalance between the level of pro-oxidant species and antioxidative defense, resulting in lipid peroxidation (Puppel et al, 2014) as observed in Caddisfly larvae Hydropsyche exocellata (Barata et al, 2005) exposed to Cd. The latent long-term exposure of bees to metals deserves further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The exhaustion of antioxidant systems is one of the reasons for the occurrence of oxidative stress, which results in avalanche production of reactive oxygen or free radicals. High oxidative stress is common in organs and tissues with high metabolic and energy demands, including skeletal and heart muscle, liver and blood cells . Milk composition can be altered by the feeding regime .…”
Section: Introductionmentioning
confidence: 99%
“…High oxidative stress is common in organs and tissues with high metabolic and energy demands, including skeletal and heart muscle, liver and blood cells. 5 Milk composition can be altered by the feeding regime. 6 -13 Antioxidants can be transferred either directly from the feed to the milk, 14 or indirectly, diet supplements cows' milk.…”
Section: Introductionmentioning
confidence: 99%
“…However, although numerous hypotheses for the pathogenesis of this disease, including lipid metabolism disorder, intravascular coagulation, microvascular injury, and intraosseous hypertension5678, have been proposed, the exact mechanism of steroid-induced osteonecrosis of the femoral head (ONFH) still remains unclear. Yet, among all the risk factors reported, oxidative stress disorders may be one of the most common one participated9, which may benefit more when intervened.…”
mentioning
confidence: 99%